Effect of lake-water budget management preferences on optimum operating conditions and neighboring basins interacting: case of Lake Beyehir (Turkey) - Sanli, Ahmet Sancak; Kesgin, Erdal; Tan, R. Ilayda; Agaccioglu, Hayrullah; Demir, Ibrahim; Sinan, Ilke (SPRINGER INT PUBL AG, 2022)
In the presented study, considering the case of Lake Beyehir, Turkey's largest freshwater lake, hydrological factors and the value judgments of people in different social groups benefiting from the lake about water use were analyzed, and the water budget factors were revealed. An optimization model was developed by obtaining the relative importance values of water use. The value judgments of the people who benefit from the lake were obtained by adapting the Analytical Hierarchical Process (AHP) method, which is one of the statistical methods used in multi-qualified decision-making problems, to the study. The plant water requirement of the agricultural lands irrigated from the lake was determined. The hydrological and mathematical correlations necessary for the optimization model were obtained by analyzing precipitation, evaporation, runoff, groundwater levels, and lake water level. It is aimed to reveal the relationship between the subjective judgments of the decision-makers and the objective hydrological factors by synthesizing water importance values obtained with AHP and measurement data. Consequently, a numerical model that shows the optimum level of operation of the lake under possible climatic conditions and usage habits predicts how much water can be drawn from the lake for irrigation and urban use and estimates water budget variables.
Keywords: Lake management; Optimization; AHP; Lake Beyehir; GAMS; ALLOCATION; Water Resources